2021
DOI: 10.3390/en14102792
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Magnetic Field Exciter for Direct Testing of Magnetocaloric Materials’ Properties

Abstract: The paper presents research on magnetic field exciters dedicated to testing magnetocaloric materials (MCMs) as well as used in the design process of magnetic refrigeration systems. An important element of the proposed test stand is the system of magnetic field excitation. It should provide a homogeneous magnetic field with a controllable value of its intensity in the MCM testing region. Several concepts of a magnetic circuit when designing the field exciters have been proposed and evaluated. In the MCM testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Lyskawinski et al. [ 64 ] also revealed that the magnetic heating method was compared with the traditional method, which confirmed its feasibility. However, it should be noted that the energy efficiency of the magnetocaloric cycle is low, the temperature span caused by each cycle is limited, and its current heating capacity depends heavily on the cycle efficiency.…”
Section: Magnetocaloric Effectmentioning
confidence: 91%
“…Lyskawinski et al. [ 64 ] also revealed that the magnetic heating method was compared with the traditional method, which confirmed its feasibility. However, it should be noted that the energy efficiency of the magnetocaloric cycle is low, the temperature span caused by each cycle is limited, and its current heating capacity depends heavily on the cycle efficiency.…”
Section: Magnetocaloric Effectmentioning
confidence: 91%
“…stepper motors [38], brushless direct current machines [11,30], levitation systems (linear motors) [31] as well as in wireless power transfer systems [17], magnetic field excitation systems [23] and other electromagnetic converters.…”
Section: Introductionmentioning
confidence: 99%